2008
DOI: 10.1261/rna.1100708
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X mental retardation protein interactions with the microtubule associated protein 1B RNA

Abstract: Fragile X mental retardation syndrome, the most common form of inherited mental retardation, is caused by the absence of the fragile X mental retardation protein (FMRP). FMRP has been shown to use its arginine-glycine-glycine (RGG) box to bind to a subset of RNA targets that form a G quadruplex structure. We performed a detailed analysis of the interactions between the FMRP RGG box and the microtubule associated protein 1B (MAP1B) mRNA, a relevant in vivo FMRP target. We show that MAP1B RNA forms an intramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 55 publications
3
82
0
Order By: Relevance
“…FMRP binds tightly to G-quadruplexes in the 5Ј-UTRs of protein phosphatase 2A catalytic subunit and MAP1B (microtubule-associated protein 1B), and it was suggested that this interaction represses translation of both mRNAs (77,80). Furthermore, it was demonstrated that the FMRP-G-quadruplex repressor in the MAP1B 5Ј-UTR was destabilized by an increased FMRP concentration, suggesting that the variation of FMRP concentration in response to neuronal stimulation might act as a regulatory switch from translational repressor to a translational activator (43). The RGG box of FMRP was shown to be responsible for the interaction with the G-quadruplex secondary structure in the MAP1B 5Ј-UTR (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMRP binds tightly to G-quadruplexes in the 5Ј-UTRs of protein phosphatase 2A catalytic subunit and MAP1B (microtubule-associated protein 1B), and it was suggested that this interaction represses translation of both mRNAs (77,80). Furthermore, it was demonstrated that the FMRP-G-quadruplex repressor in the MAP1B 5Ј-UTR was destabilized by an increased FMRP concentration, suggesting that the variation of FMRP concentration in response to neuronal stimulation might act as a regulatory switch from translational repressor to a translational activator (43). The RGG box of FMRP was shown to be responsible for the interaction with the G-quadruplex secondary structure in the MAP1B 5Ј-UTR (43).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the formation of G-quadruplex secondary structures within 5Ј-UTRs results in translational repression of a number of different mRNAs, including N-ras, Zic-1, membrane-type matrix metalloproteinase 3, ESR-1, and Bcl-2 (35)(36)(37)(38)(39)(40)(41)(42). Similar to the IRE stem loop, the stability of G-quadruplex structures could be modulated by RNA binding proteins such as FMRP or members of the hnRNP A family (43,44).…”
mentioning
confidence: 99%
“…Naturally occurring G-quadruplexes targeted by FMRP adopt multiple conformations and are challenging to study by structural methods (27,28). Therefore, detailed structural information about RGG recognition of G-quadruplexes has been mostly obtained from studies on sc1 RNA (21), the RNA selected against the entire human FMRP but shown to require only the RGG motif of the protein for high affinity and specific binding (29,37,38).…”
Section: Significancementioning
confidence: 99%
“…Some of these RNAs harbor motifs that may form G-quartets and G-quadruplexes in vivo (21, 25). Several mRNAs contain regions shown to form G-quadruplexes implicated in FMRP binding in vitro (21,24,(26)(27)(28)(29). Notably, binding of FMRP to G-rich RNAs in vitro requires only the RGG motif, which specifically interacts with natural and in vitro selected G-quadruplex-containing RNAs such as a 35-nucleotide sc1 RNA (21,(26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation